Hermansky–Pudlak syndrome: Mutation update. Issue 3 (23rd January 2020) - Huizing, Marjan; Malicdan, May C. V.; Wang, Jennifer A.; Pri‐Chen, Hadass; Hess, Richard A.; Fischer, Roxanne; O'Brien, Kevin J.; Merideth, Melissa A.; Gahl, William A.; Gochuico, Bernadette R.
Abstract: Hermansky–Pudlak syndrome (HPS) is a group of 10 autosomal recessive multisystem disorders, each defined by the deficiency of a specific gene. HPS‐associated genes encode components of four ubiquitously expressed protein complexes: Adaptor protein‐3 (AP‐3) and biogenesis of lysosome‐related organelles complex‐1 (BLOC‐1) through ‐3. All individuals with HPS exhibit albinism and a bleeding diathesis; additional features occur depending on the defective protein complex. Pulmonary fibrosis is associated with AP‐3 and BLOC‐3 deficiency, immunodeficiency with AP‐3 defects, and gastrointestinal symptoms are more prevalent and severe in BLOC‐3 deficiency. Therefore, identification of the HPS subtype is valuable for prognosis, clinical management, and treatment options. The prevalence of HPS is estimated at 1–9 per 1, 000, 000. Here we summarize 264 reported and novel variants in 10 HPS genes and estimate that ~333 Puerto Rican HPS subjects and ~385 with other ethnicities are reported to date. We provide pathogenicity predictions for missense and splice site variants and list variants with high minor allele frequencies. Current cellular and clinical aspects of HPS are also summarized. This review can serve as a manifest for molecular diagnostics and genetic counseling aspects of HPS.